Dakwah melalui Seni Perspektif Hadis - Jamaludin, Fitah (Fakultas Dakwah UIN KHAS Jember, 2023)
Dawah is one of the ways to convey the mission of the Prophet Muhammad, so dawah activities have been carried out since the time before the Prophet Muhammad. However, dawah has various ways in its delivery, which requires preachers to be more creative in conveying their dawah messages. Dawah can be delivered through print media, lectures, and using art in its implementation. From this issue, several research questions are formulated, including: 1) What is the meaning of dawah and art? 2) What is the intersection between dawah and art? 3) What is the Hadith's view on dawah through an art approach? This study used a qualitative research model and a literature review method, where references used were books and Hadith books that support this research. The research approach used in this study is a social approach, considering that dawah is a social interaction activity that involves interacting with the community. The study concluded that dawah is an activity of conveying the mission of the Prophet, while art is a form of beauty expressed through works, and the intersection between dawah and art is the same in wanting to convey the message contained in dawah and art. Moreover, from the Hadith perspective, dawah through art is permissible because it falls under the category of wisdom when conveying dawah.